If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -1y + 1 = 13 Reorder the terms: 1 + 4y + -1y = 13 Combine like terms: 4y + -1y = 3y 1 + 3y = 13 Solving 1 + 3y = 13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3y = 13 + -1 Combine like terms: 1 + -1 = 0 0 + 3y = 13 + -1 3y = 13 + -1 Combine like terms: 13 + -1 = 12 3y = 12 Divide each side by '3'. y = 4 Simplifying y = 4
| 5x^2+3x+24=47 | | 20=m+1 | | (2y+3)-4=9 | | k=1.6d+300 | | 3q=18 | | 10z=9z-11 | | 41=5w-9 | | a+2(a-3)=15 | | 4+4x=-24 | | -6+2*y=0 | | j+6=9 | | 7x-15=4x-6 | | -2+2*y=0 | | 6=2p | | 2u-7=-19 | | 6+2*y=0 | | 173-w=224 | | 6(y-3)=6y+7 | | n/9=16/24 | | -11=4v+5 | | 4x^2-49+12=0 | | 4v-15=45 | | -5x=3y | | -6-2y=0 | | 3+4u=-25 | | 3X-15=7x+80 | | 46=3w+10 | | 9/n=4/8 | | -5x+5y=8 | | ln(4x-2)=24 | | x^3=(1/27) | | lnx=13 |